The effect of partitioned framing vs. all-inclusive framing of donation amount on prosocial behavior: focus on the moderation effect of psychological characteristics - Lee, Eun Young; Chu, Kyounghee (Frontiers in Psychology, 2023)
Despite numerous studies on individual charitable donations and cause-related marketing have been conducted, the framing of the donation amount has not been studied. This research suggests that people's intention to donate to charity differs depending on whether the donation amount is framed as all-inclusive or partitioned. The main effect of partitioned framing was moderated by individual differences in the need for cognition and regulatory focus. The results of our research are threefold. First, people responded more positively to engage in prosocial behavior in the partitioned donation amount condition than in the all-inclusive condition, even when the total amounts were the same. Second, the framing effect of the donation amount differed according to the need for cognition. Individuals with a high need for cognition (NFC) had a higher intention to donate in the partitioned donation amount condition than in the all-inclusive condition, while individuals with low NFC did not show differences in either condition. Third, the framing effect of the donation amount differed according to regulatory focus. Prevention-focused individuals were more willing to donate in the partitioned condition than in the all-inclusive condition, while promotion-focused individuals did not show differences in either condition. In addition, the interaction of framing and regulatory focus on donation intention was mediated by the perceived authenticity of the donation organization. This research has several academic and practical implications for effective corporate social responsibility activities.